Peran Hubungan Masyarakat (Humas) Dalam Penyebarluasan Informasi Pembangunan Daerah di Kabupaten Bengkalis Riau - Suryani Barimbing; Yunisa Octavia (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2022)
The purpose of this analysis is to be able to find out and also analyze how the strategies that can be used by the public relations of the Riau City government in disseminating regional development information. As for the participation of local governments, namely to be able to build